Propranolol-induced dramatic improvement of ulcerated vulvar hemangioma. - Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 65-day-old baby girl was first observed for the presence of a vulvar ulcerated hemangioma. Her mother reported that at birth there was a flat red patch that in the subsequent weeks had become raised and for a week deeply ulcerated. The physical examination showed a 3 x 2 cm red plaque of the right vulvar region, hotter than the surrounding skin, with a 1 cm deep ulceration (Fig. 1). The clinical history and physical data led to the final diagnosis of ulcerated hemangioma. We recommended fusidic acid ointment every diaper change, a cotton diaper without outer plastic layer when the baby was awake and left decubitus. Moreover, oral propranolol 2mg/kg per day was started. On the control examination after 35 days the ulcer was closed and hemangioma was reduced to a peripheral erythematous rim.